2006
DOI: 10.1021/jp0662754
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of Novel Polycyclic Aromatic Polymers

Abstract: A series of novel polyphenylenevinylene (PPV) derivative polymers were studied by absorption and photoluminescence spectroscopies. The effect of the sequential introduction of polycyclic aromatic ring substituents into the delocalized backbone was examined with relation to hypsochromatic and bathochromatic shifting. While the replacement of the phenyl units by naphthyl units results in a substantial hypsochromic shift of both the absorption and emission spectra, their subsequent substitution by anthryl units r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…4. The emission of POPV was recorded at 550 nm, which had been established as the peak emission wavelength [17]. A deconvolution fit gives a lifetime of 1.16 ns for the POPV polymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4. The emission of POPV was recorded at 550 nm, which had been established as the peak emission wavelength [17]. A deconvolution fit gives a lifetime of 1.16 ns for the POPV polymer.…”
Section: Resultsmentioning
confidence: 99%
“…1, it has been demonstrated that both the electronic and vibrational activities of these complex systems can be controlled and optimized by systematic variation of the polymer conjugated backbone [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A further discussion of the adapted model and its observed trend is outside the scope of this paper and can be found elsewhere. 40 …”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the systematic variation of the vibrational coupling along the backbone results in a systematic decrease in the non-radiative decay rates and thus an optimisation of the radiative yield. The systematic variation of the electron density of the vinylene bond of the polymer series by the introduction of naphthalene and anthracene moieties into the backbone [9,10,11] suggests that the photo-active stability can be similarly improved. This report presents a systematic study of the relative stabilities of polymers 1-6 ( Figure 1 The mechanisms and results of such degradation in conjugated polymers have been studied and presented at length in the literature [12].…”
Section: Introductionmentioning
confidence: 99%